2003
DOI: 10.1209/epl/i2003-00128-3
|View full text |Cite
|
Sign up to set email alerts
|

Atomic correlations in itinerant ferromagnets: Quasi-particle bands of nickel

Abstract: We measure the band structure of nickel along various high-symmetry lines of the bulk Brillouin zone with angle-resolved photoelectron spectroscopy. The Gutzwiller theory for a nine-band Hubbard model whose tight-binding parameters are obtained from non-magnetic density-functional theory resolves most of the long-standing discrepancies between experiment and theory on nickel. Thereby we support the view of itinerant ferromagnetism as induced by atomic correlations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(72 citation statements)
references
References 30 publications
6
65
1
Order By: Relevance
“…8,12 In contrast, for Ni, band structure calculations could not describe the photoemission satellite at 6-eV BE and, in addition, compared to the LSDA band structure calculations of the 3d bands, a substantial (highenergy) mass-enhancement factor between 1.3 and 1.5 was obtained. [21][22][23][24][25][26] More recent (S)ARPES studies revealed also for Fe and Co considerable many-body effects. For Fe at high binding energies mass renormalizations up to a factor of 1.3 have been detected.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…8,12 In contrast, for Ni, band structure calculations could not describe the photoemission satellite at 6-eV BE and, in addition, compared to the LSDA band structure calculations of the 3d bands, a substantial (highenergy) mass-enhancement factor between 1.3 and 1.5 was obtained. [21][22][23][24][25][26] More recent (S)ARPES studies revealed also for Fe and Co considerable many-body effects. For Fe at high binding energies mass renormalizations up to a factor of 1.3 have been detected.…”
Section: Introductionmentioning
confidence: 98%
“…8 Among the various more recent attempts to calculate the influence of correlation effects on the spectral function of the ferromagnetic 3d transition metals we mention here recent DMFT calculations 18,31,40,43 on Fe, Co, and Ni, 3BS calculations on Fe and Co 31,39,40 and Gutzwiller theory 44,45 calculations on Ni. 26 In the present work we focus on SARPES studies on Ni and combine them with extended results of our previous SARPES studies 31,40 on Fe and Co to give a complete comparative overview on how spin-dependent electronic correlations influence the ferromagnetic 3d transition metal series. We emphasize that we cannot resolve the low-energy contributions to the mass renormalization and therefore only deal with the high-energy contributions due to correlation effects.…”
Section: Introductionmentioning
confidence: 99%
“…The class of variational wave functions for which our formulae apply goes much beyond our previous investigations [29,30,31]. First, the Gutzwiller correlator now employs projections onto eigenstates of an effective atomic Hamiltonian which makes the variational Hilbert space much more flexible with respect to local correlations.…”
Section: Scope Of This Workmentioning
confidence: 99%
“…There is no simple recipe for the most efficient way to implement these constraints in the numerical minimization procedure. In previous works [29,30] we have proposed the following strategy: We perform a transformation of the local orbital basis onto a new one in which the local density matrix is diagonal. In this new basis, the main (2N o ) 2 constraints could then be implemented by the diagonalization of a 2N o -dimensional matrix which we called the 'Z-matrix'.…”
Section: Effective Single-particle Hamiltonian For Nickelmentioning
confidence: 99%
“…[10][11][12] The trial wavefunction is chosen to include the minimum basis set with variational parameters. The Gutzwiller wavefunction (GW) [13][14][15] is one of the popular ansatz, and has been applied to a number of correlated electron systems such as Ni 16) and Fe pnictides. 17,18) The method has been extended to the first-principles version on the basis of the LDA+U Hamiltonian.…”
Section: Introductionmentioning
confidence: 99%